Методология расчета параметров контактов с жидкометаллическим эффектом, для многоамперных автоматических выключателей - Павленко, Татьяна Павловна (НТУ "ХПИ", 2016)
Создание конструкций многоамперных автоматических выключателей со значительными величинами номинальных токов требуют изменения и повышения характеристик их контактных систем, которые определяют энергоемкость, материалоемкость, экономичность и другие параметры. Учитывая особенности составов композиций в контактных системах многоамперных автоматических выключателей и их многоступенчатую конструкцию, в данной работе рассмотрены перспективные составы бессеребряных контактов и расчет их основных параметров. В основу методологического расчета положены методы определения энергетических параметров, отображающие особенности работы контактных систем с жидкометаллическим эффектом.

Determination of the energy parameters of promising structures without silver contact with liquid metal effect for high current circuit-breakers. Based on the analysis of the contact systems containing electrical contacts with liquid metal effect, determine their parameters, which determine the electro dynamic stability and energy high current circuit-breakers. The features of models for calculating the main parameters of a liquid-metal contacts (GMK), and a pseudo-liquid-metal contacts (PGMK), intended for the main contacts for high current circuit-breakers. The basis for calculating the parameters of the effect lies conductivities phase changing material properties under the influence of temperature. Display and analyze the calculation model of conduction in the three-dimensional field for the liquid-metal contact with the mesh being. Identify the most promising design silver contacts, which are based on liquid-metal-effectiveness ones. We compared the composition of liquid metal contacts (GMK) with a mesh base and pseudo liquid metal contacts (PGMK), whose operation is based on the change of the aggregate state during operation. Calculation feature parameters PZGMK is a mathematical model of the contacts, which allows to determine the geometric parameters of conducting a heterogeneous surface. For the first time shown in the methods of calculation of the dependence of the material parameters of contact systems of contact pads and shapes, with state-of the contact surface, contact pressure, the value of the flowing current. The promising designs of electric for high current circuit-breakers for the first time reflected the composition of solid contacts (PGMK), which during operation act asliquid-metal contacts (GMK). A feature of the composition of such contacts is to have solid metal matrix in the pores of which are low-melting component. For contact PGMK analysis model, distribution of filler material on a conductive surface and the parameters of the porosity of the base material. It is shown that the method of solution, the problem of determining the transition resistance in the ground contacting surface of the contacts. The use of such contacts in the main contact high current circuit breakers and other electrical switching apparatus with current without switching arc to the sustainability of their electro dynamic, reduced transient resistance in comparison with silver-containing compositions, reduced size and weight designs of circuit breakers by using a lightweight mechanism for trip free.
The methodology for calculating the parameters of contact with liquid metal effect for high current circuit-breakers
Keywords: многоамперный автоматический выключатель; бессеребряные контакты; составы композиций; энергетические параметры; структуры композиций